Composição e estrutura de comunidades de anuros nos Campos Gerais do sul do Brasil : efeitos dos fatores biológicos, ambientais e espaciais. - Batista, Vinicius Guerra (2014)
The community ecology seeks to understand the factors that are structuring communities and allowing species coexistence. The knowledge of these mechanisms is still incipient for anuran amphibians, especially in relation to the effects of dispersion, habitat selection and responses to environmental, biological and spatial characteristics. Amphibian communities present distinct patterns in a range of spatial, temporal and functional scale. The knowledge of the factors responsible to structure the dynamics of these communities and species distribution are useful tools, allowing the understand of the effects of populations declines, especially considering that the anurans are among the most threatened group of vertebrates, mainly by human activities. Anthropogenic pressures and agricultural activities have become Campos Gerais one of the most threatened ecosystems in Brazil, making it urgent to develop studies on the fauna of this region. We recorded species of amphibians into disjoint remnants of Cerrado and ecotone (Atlantic Forest) in Campos Gerais of Paraná. The results are presented in two parts, the first (i) "Composition and structure of anuran assemblies in the Cerrado-Atlantic Forest ecotone in Campos Gerais in southern Brazil", and the second chapter (ii) "Effects of biological, environmental and spatial factors structuring the tadpoles metacommunity in southern Brazil". It was possible to verify differences in species composition between different environments as well as understand patterns of shaping an anuran metacommunity.